The Influence Of The Work Environment On Employee Performance With Supervision As A Moderator At The Tourism Office, Culture, Youth And Sports Of Dairi Regency - Jumali; Abdi Sugiarto (International Journal of Management, Economic and Accounting, 2025)
The purpose of this study is to find out and analyze the influence of the Work Environment on Performance mediated by Supervision at the Office of Tourism, Culture, Youth and Sports of Dairi Regency. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 96 people. The results of data analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) show that the Work Environment has a significant influence on employee performance (T-statistic 2,102 > 1.96; P-value 0.038 < 0.05), which indicates that improving the Work Environment directly improves employee performance. The Work Environment also has a positive and significant effect on Supervision (T-statistics: 5,595 > 1.96; P-value 0.000 < 0.05), indicating that the improvement of the Work Environment significantly improves employee supervision. Furthermore, supervision had a positive and significant effect on Performance (T-statistics 25,408 > 1.96; P-value 0.000 < 0.05), which means that the increase in Supervision significantly improves Performance. Indirect influence analysis showed that Supervision was able to moderate the influence between Work Environment and Performance (T-statistic 6,008 > 1.96; P-value 0.000 < 0.05). These findings provide insight that Supervision plays a significant mediator role in the relationship between the Work Environment and Performance, emphasizing the importance of Supervision in improving employee Performance.